Răspuns :
Explicație pas cu pas:
metoda reducerii:
[tex]\left \{ {{3x+2(1-y) = 20} \atop {2(2x+1)-3(2y + 1) = 7}} \right. \\ [/tex]
[tex]\left \{ {{3x + 2 - 2y = 20} \atop {4x + 2 - 6y - 3 = 7}} \right. \\[/tex]
[tex]\left \{ {{3x - 2y = 18} | \cdot ( - 3)| \atop {4x - 6y = 8} \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: } \right. \\ [/tex]
[tex]\left \{ {{ - 9x + 6y = - 54} \atop {4x - 6y = 8} \: \: } \right. \\ [/tex]
------
[tex] - 5x = - 46 = > \bf x = \frac{46}{5} \\ [/tex]
[tex]4 \cdot \frac{46}{5} - 6y = 8 \\ 6y = \frac{184}{5} - 8 \\ 6y = \frac{144}{5} = > \bf y = \frac{24}{5} [/tex]
b)
[tex]\left \{ {{2x-y = -1} \atop {1-2x-y = -1}} \right. \\ [/tex]
[tex]\left \{ {{2x-y = -1} \atop {-2x-y = -2}} \right. \\ [/tex]
----
[tex] -2y = -3 = > \bf y = \frac{3}{2} \\ [/tex]
[tex] 2x - \frac{3}{2} = -1 <=> 2x = \frac{1}{2} = > \bf x = \frac{1}{4} \\ [/tex]